The Disputes Arising from the Real Estate Book in Algerian Legislation - Fadli, Sid ali (Journal of Legal Studies and Researches, 2023)
The real estate book is closely related to the general survey of lands because it is placed on the basis of the real estate cards established after the creation of the survey process. Which is a solid proof of property ownership and I particularly study in this article the real estate book in terms of its essence, its cancellation and the implications thereof and the disputes that arise in connection with it.